2021
DOI: 10.3389/fgene.2021.659500
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Differentiation Between Indica and Japonica Rice Root Tip Responses to Different Environments Based on Single-Cell RNA Sequencing

Abstract: Background: As Oryza sativa ssp. indica and Oryza sativa ssp. japonica are the two major subspecies of Asian cultivated rice, the adaptative evolution of these varieties in divergent environments is an important topic in both theoretical and practical studies. However, the cell type-specific differentiation between indica and japonica rice varieties in response to divergent habitat environments, which facilitates an understanding of the genetic basis underlying differentiation and environmental adaptation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In contrast to OsBRI1, qPH1.1 showed no significant difference in leaf sheath, leaf angle, and longitudinal cell elongation, which implied that the BR signal transduction pathway showed less effect on qPH1.1 [ 106 ]. Our ongoing exploration of this qPH1.1 will focus on the gene regulatory network by gene prediction and RNA-sequencing, which may disclose the potential mechanism [ 107 ]. The stem diameter of ZN6 is significantly larger than 93-11, which makes the ZN6 higher biomass and is resistant to lodging to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to OsBRI1, qPH1.1 showed no significant difference in leaf sheath, leaf angle, and longitudinal cell elongation, which implied that the BR signal transduction pathway showed less effect on qPH1.1 [ 106 ]. Our ongoing exploration of this qPH1.1 will focus on the gene regulatory network by gene prediction and RNA-sequencing, which may disclose the potential mechanism [ 107 ]. The stem diameter of ZN6 is significantly larger than 93-11, which makes the ZN6 higher biomass and is resistant to lodging to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies demonstrated that the mesophyll tissue plays a prominent role in leaf response to salt, heat, and drought stress. In rice, salt causes the proliferation, differentiation, and maturation of the mesophyll to be postponed, resulting in a reduced number of mesophyll cells [60]. Initially captured by single-cell profiling, the effect on mesophyll development was biologically confirmed, illustrating the power of single cell RNA sequencing (scRNA-seq) not only to detect transcriptome changes, but also to suggest changes in organ composition.…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…Recently, it has become increasingly utilized in different plant species to characterize gene regulation at the single-nuclei level. Species such as Arabidopsis thaliana [4][5][6][7][8][9][10], Zea mays [11][12][13], Oryza sativa [14][15][16], and Nicotiana attenuata [17] make up the majority of data generated to date when it comes to plant tissue studied.…”
Section: Introductionmentioning
confidence: 99%